Microbial production of xylitol from D-xylose and sugarcane bagasse hemicellulose using newly isolated thermotolerant yeast Debaryomyces hansenii - Prakash, Gyan; Varma, Anjanikumar; Prabhune, Asmita; Shouche, Yogesh; Rao, Mala (Bioresource Technology, 2011)
A thermotolerant yeast capable of fermenting xylose to xylitol at 40 C was isolated and identified as a strain of Debaryomyces hansenii by ITS sequencing. This paper reports the production of xylitol from D-xylose and sugarcane bagasse hemicellulose by free and Ca-alginate immobilized cells of D. hansenii. The efficiency of free and immobilized cells were compared for xylitol production from D-xylose and hemicellulose in batch culture at 40 degrees C. The maximum xylitol produced by free cells was 68.6 g/L from 100 g/L of xylose, with a yield of 0.76 g/g and volumetric productivity 0.44 g/L/h. The yield of xylitol and volumetric productivity were 0.69 g/g and 0.28 g/L/h respectively from hemicellulosic hydrolysate of sugarcane bagasse after detoxification with activated charcoal and ion exchange resins. The Ca-alginate immobilized D. hansenii cells produced 73.8 g of xylitol from 100 g/L of xylose with a yield of 0.82 g/g and volumetric productivity of 0.46 g/L/h and were reused for five batches with steady bioconversion rates and yields. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Immobilization; Sugarcane bagasse hemicellulose; Thermotolerant Debaryomyces hansenii; xylitol; Xylose

Crystalline xylitol production by a novel yeast, pichia caribbica (HQ222812), and its application for quorum sensing inhibition in gram-negative marker strain chromobacterium violaceum CV026 - Mukherji, Ruchira; Joshi-Navare, Kasturi; Prabhune, Asmita (Applied Biochemistry and Biotechnology, 2013)
Xylitol, a sugar alcohol, is fast gaining ground over other artificial sugar substitutes owing to its advantageous properties. Xylitol is a safer alternative for diabetics because of insulin-independent metabolism. It has beneficial properties suitable to form an important part of odontological formulations. Conventional commercial production of xylitol involves harsh chemical method operating at high temperature and pressure. Thus, microbial production of xylitol is preferred over chemical method, and yeasts have been extensively exploited for this purpose. In the present manuscript, quantitative production of xylitol from d-xylose with the yield of 0.852 gm/gm and volumetric productivity of 1.83 gm/l/h in crystalline form, using novel yeast Pichia caribbica is reported. Also, a mild, safe procedure for product extraction is described. The ability of xylitol to act as a quorum sensing antagonist in gram-negative marker strain Chromobacterium violaceum CV026 has been demonstrated for the first time.
Keywords: Crystallization; CV026; Pichia caribbica; Quorum sensing antagonist; xylitol

Xylitol production by cyberlindnera (Williopsis) saturnus, a tropical mangrove yeast from xylose and corn cob hydrolysate - Kamat, S.; Gaikwad, S.; Kumar, A. Ravi; Gade, Wasudeo N. (Journal of Applied Microbiology, 2013)
AimPotential for xylitol production from xylose and corn cob hydrolysate by a tropical mangrove yeast. Methods and ResultsIn the present study, 21 fungi were isolated from detritus-based mangrove wetlands along the Indian west coast. Of these, one yeast isolate had the ability to grow and assimilate xylose producing significant amounts of xylitol (3863gl(-1)). A maximum yield of 054gg(-1) was obtained after 144h of growth on xylose (150gl(-1)) and corn cob hydrolysate (CCH, containing 65gl(-1) xylose). Using biochemical and molecular methods, the yeast was identified as Cyberlindnera (Williopsis) saturnus. Preliminary characterization of enzymes in the cell-free extract revealed that while xylose reductase (XR) preferred NADPH to NADH as cofactor, xylitol dehydrogenase (XDH) was NAD specific. ConclusionsSignificant amounts of xylitol could be produced on CCH using C.saturnus isolated from tropical mangrove wetlands. The yeast has the potential to assimilate rather than ferment xylose as its XR has a preference for NADPH. Significance and Impact of the StudyMicrobes offer an economically viable and green approach for production of xylitol, an industrially important compound. A mangrove ecosystem with its battery of lignocellulolytic enzymes is an ideal location for isolating fungi capable of producing xylitol from agroindustrial waste such as CCH.
Keywords: corn cob hydrolysate; Cyberlindnera; mangrove; Williopsis; xylitol; Xylose; Yeast

Energy and life cycle impact assessment for xylitol production from corncob - Dasgupta, Diptarka; Sidana, Arushdeep; Ghosh, Prasenjit; Sharma, Tripti; Singh, Jasvinder; Prabhune, Asmita; More, Snehal; Bhaskar, Thallada; Ghosh, Debashish (Journal of Cleaner Production, 2021)
The conversion of biobased feedstocks into energy and value-added chemicals is one main approach to address the current global challenge for waste mitigation through the biorefinery mode. Corncob biomass which is one of the most abundant agricultural residue in India with a high hemicellulose content, can serve as a potential low-cost raw material for food-grade xylitol production. The present study demonstrates a process for xylitol production from corncob biomass with detailed energy and life cycle analysis for viability assessment. The major highlight of the process is the use of microbial fermentation, where biomass-derived D-xylose is converted to xylitol with high selectivity. Overall, 0.502 kg of xylitol crystals could be produced from 3.5 kg of corncob biomass. Simulation analysis revealed that the evaporators are the primary consumers of energy, and the process of heat integration can significantly reduce the energy requirements of the overall process. Environmental impacts of the system evaluated showed emission results of 8.68 kg CO2 equivalent and revealed that marine aquatic and freshwater eco-toxicity are the only possible contributors to the environment. The results suggest that the process would have favourable energy balances, which can be used in pilot plant and heat exchanger network design and operation for xylitol production scale up to 500 L. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: biomass valorization; Life cycle impact assessment; simulation; xylitol

Crystalline xylitol production from corncob biomass with oral toxicity analysis - Ahuja, Vishal; Dasgupta, Diptarka; Kshirsagar, Siddheshwar; Ghosh, Prasenjit; More, Snehal; Gupta, Piyush; Behera, Babita; Bhaskar, Thallada (Industrial Crops and Products, 2022)
Xylitol, a five-carbon sugar alcohol, has a steady global market and finds application as a natural sugar substitute in various food and confectionery products. Biocatalytic xylitol production, although touted as a greener alternative to conventional chemical catalysis, suffers from certain challenges, the primary being high cost of production. This study demonstrates a process for food-grade xylitol production from corncob biomass with energy reduction through two major process modifications. A non-conventional fermentation strategy was adopted whereby adjusting aeration without agitation, xylitol with high yield (0.86 +/- 0.015 g/g), and productivity (0.74 gL(-1)h(-1)) could be produced by a GRAS Pichia caribbica MTCC 5703 strain. Xylitol was recovered from the broth in the form of crystals using a combination of membrane-based filtration and crystallization. The crystals demonstrated similar to 98 % purity when quantified with H-1 NMR. Oral toxicity analysis of the crystals demonstrated no adverse effect in female Winstar rats (at a loading of 2000 mg/kg body weight of animals). Overall process statistics showed that 0.584 kg of food-grade xylitol crystals could be produced from 3.5 kg of corncob biomass. The two-process modifications during fermentation and xylitol recovery enabled an energy saving of similar to 20.842 kW/kg of crystals, providing tremendous advantages for biorefinery-based large-scale xylitol production from corncob biomass.
Keywords: Biomass; Fermentation; Oral toxicity analysis; Wastewater treatment; xylitol

Process development for crystalline xylitol production from corncob biomass by Pichia caribbica - Dasgupta, Diptarka; Sidana, Arushdeep; Sarkar, Bipul; More, Snehal; Ghosh, Debashish; Bhaskar, Thallada; Ray, Anjan (Food and Bioproducts Processing, 2022)
Xylitol, a commodity chemical, is widely used in nutraceutical and pharmaceutical formulations. Microbial xylitol production is a promising alternative to mitigate current industrial practice issues and offers an environment-friendly sustainable conversion route. This study demonstrates a bioprocess for xylitol production from corncob using a mesophilic yeast Pichia caribbica. Corncob was hydrolyzed by dilute acid and steam explosion to recover fermentable xylose and used as the feed for xylitol production. Activated carbon treatment (3% w/v) completely removed the biomass-derived inhibitors furfural and hydroxymethyl furfural from the liquid hydrolysate. The fermenting yeast Pichia caribbica produced 124.1 +/- 0.45 g/L xylitol from the detoxified and concentrated corncob hydrolysate with a high yield of 0.80 +/- 0.02 g/g. The crystallized xylitol with 96.5% purity demonstrated no harmful effects on the cell line used as a control for the in-vitro toxicity studies. This proof of concept can be applied to help scale up for bio-refinery-based large-scale production of xylitol from corncob biomass.(c) 2022 Institution of Chemical Engineers. Published by Elsevier Ltd. All rights reserved.
Keywords: Biomass; Corncob; Detoxification; Fermentation; Toxicity analysis; xylitol

Process development for detoxification of corncob hydrolysate using activated charcoal for xylitol production - Ahuja, Vishal; Kshirsagar, Siddheshwar; Ghosh, Prasenjit; Sarkar, Bipul; Sutar, Ajit; More, Snehal; Dasgupta, Diptarka (Journal of Environmental Chemical Engineering, 2022)
The work describes process development for detoxification of corncob hydrolysate using activated carbon for microbial xylitol production. Activated carbon was used as an adsorbent to completely remove the major fermentation inhibitors obtained during dilute acid and steam explosion of biomass. A xylitol yield of 0.78 g/g was achieved from the detoxified hydrolysate in a 5 L fermenter by Pichia caribbica. The spent carbon was effectively regenerated and used for three consecutive cycles of operation. The successive regeneration and reuse of carbon could reduce the operational cost by similar to 38% and be used as a reference dataset for process scale-up and cost-effective xylitol production.
Keywords: Activated charcoal; Detoxification; Fermentation; Regeneration; xylitol

Challenges and opportunities for production of C5 sugar fatty acid esters (SFAEs) from renewable resources - Tracy, Preetanshika; Dasgupta, Diptarka; More, Snehal (Industrial Crops and Products, 2023)
Sugar fatty acid esters represent a billion-dollar market with huge global demand. Although glucose and sucrose-based surfactants have prevailed in the chemical industry for decades, C-5-based esters are relatively unknown and have recently started to gain attention owing to their multifunctional properties. These molecules can be derived from cheap and inexpensive biomass/renewable resources and present promising potential with diverse applications as additives in various nutraceutical, pharmaceutical, and cosmeceutical formulations. However, large-scale production of C-5 sugar esters is limited, with one or two commercial plants operating worldwide. This review highlights the major challenges and prospects of biotechnological production of the C-5 sugar esters, considering the possible advancements over existing technology with various aspects of industrial bioprocessing and product recovery.
Keywords: Bioprocess; C-5-fatty acid esters; Lipase; solvent; xylitol

Food-grade xylitol production from corncob biomass with acute oral toxicity studies - Dasgupta, Diptarka; Ahuja, Vishal; Singh, Raghuvir; More, Snehal; Mudliar, Sandeep; Kumar, Madan (World Journal of Microbiology & Biotechnology, 2023)
Xylitol, a sugar substitute, is widely used in various food formulations and finds a steady global market. In this study, xylitol crystals were produced from corncob by fermentation (as an alternative to the chemical catalytic process) by a GRAS yeast Pichia caribbica MTCC 5703 and characterized in detail for their purity and presence of any possible contaminant that may adversely affect mammalian cell growth and proliferation. The acute and chronic oral toxicity trials demonstrated no gross pathological changes with average weekly weight gain in female Wistar rats at high xylitol loading (LD50 > 10,000 mg/kg body weight). The clinical chemistry analysis supported the evidence of no dose-dependent effect by analyzing blood biochemical parameters. The finding suggests the possible application of the crystals (> 98% purity) as a food-grade ingredient for commercial manufacture pending human trials.
Keywords: Acute oral toxicity; Corncob; Fermentation; Shelf life analysis; xylitol